Jatropha oil as diesel substitute - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In rural areas, the dependence on engines run on diesel fuel for running water pumps, generators, grinding mills etc. is of paramount importance. Imported fuel is expensive and several alternatives have been sought. Jatropha curcas L. was brought...